Characterisation of aluminium release by the enFlow® fluid‐warming system in crystalloids and blood products. (7th May 2019) - Taylor, M. H.; Choi, D.; Fitzpatrick, S. M.; Gunn, K. N.
Summary: The use of uncoated aluminium‐heated plates in an intravenous fluid‐warming system has been shown to produce high levels of aluminium in Sterofundin 1/1E, a balanced crystalloid solution. However, the effect of this fluid‐warming device on other balanced crystalloid solutions and blood products has not been studied. Using mass spectrometry we measured aluminium levels in Plasma‐Lyte 148, compound sodium lactate solution, 4% human albumin solution, expired resuspended packed red cells and fresh frozen plasma that were pumped through an enFlow ® fluid‐warming system at 2 ml.min −1 . Samples were taken at baseline before heating and then at 10‐min intervals up to 60 min with the system set to warm the fluids to 40 °C. High concentrations of aluminium were found for Plasma‐Lyte 148 and compound sodium lactate solutions (mean (SD) 223 (0.6) μmol.l −1 and 163 (0.2) μmol.l −1 at 60 min, respectively); both concentrations were significantly greater than the United States Food and Drug Administration recommended maximum limit for aluminium in intravenous nutrition of 25 μg.l −1 (0.9 μmol.l −1 ). Lower aluminium levels were found in 4% human albumin solutions, expired resuspended red cells and fresh frozen plasma at 60 min (mean (SD) 5.7 (0.1) μmol.l −1, 2.7 (0.0) μmol.l −1 and 2.3 (0.4) μmol.l −1, respectively). The process allowing addition of aluminium to be added to Sterofundin 1/1E by the enFlow fluid warmer also occurs in Plasma‐Lyte 148 and compound sodium lactate solutions and to a lesser degree in blood products. The exact mechanism facilitating this process and its clinical significance remain unclear.